Mapping of Antenatal Care Visits for Pregnant Women on the risk of pregnancy and prevention of childbirth complications - Purnama Handayani; Suhartini; Iswandi Idris (Science Midwifery, 2022)
Maternal and infant mortality rates in North Sumatra are still high. Based on data from the North Sumatra Health Office as of June 2021, there are 67,345 pregnant women who have received pregnancy services, 65,431 who gave birth and 39,375 newborns. The most common causes of death for pregnant women according to the Sample Registration System (SRS) are hypertension in pregnancy 33.7%, obstetric bleeding 27.3%, non-obstetric complications 15.7% and other obstetric complications 12.04%. Antenatal Care (ANC) as one of the early screening efforts of pregnancy risk factors. The aim of the study was to map Antenatal Care Visits to Pregnant Women on the risk of pregnancy and the prevention of childbirth complications based on the minimum standards of antenatal care and danger signs during pregnancy. The method used is the spider web test, frequency test, reliability test, coefficient of determination test, bivariate analysis. The sample in this study used a non-probability sampling technique — accidental sampling, 60 samples, 2 dependent variables and 1 independent variable. The results showed that the implementation of the Mapping of Antenatal Care Visits for Pregnant Women in the working area of ​​the Sei Mencirim Health Center had not yet run optimally. This situation can be seen from the results of achieving the target of Antenatal Care Visits at the Sei Mencirim Health Center. The low achievement can be seen from the lack of cooperative respondents in filling out the questionnaire, and the education level of many who are still in elementary/junior high school. The occupation is dominated by housewives. In terms of age, it is dominated by the age of 21-30 years. Although the human resources on Puskesmas are sufficient, the availability of facilities and infrastructure does not meet government standards, and so the source of the budget obtained for Antenatal Care Visits is low. Simultaneously, knowledge about the danger signs of pregnancy and knowledge about antenatal care visits has an effect of 22.3% on knowledge about prevention of childbirth complications